Perceptions of the use of a blended learning approach to improve student performance in web development courses in selected South African higher education institutions. - Hungwe, Taurai (My University, 2013)
A Blended Learning (BL) approach is an effective approach in integrating the face-to-face methodology and the use of information communication technologies into teaching and learning. Blended Learning provides students with the best practices from both rich traditional classroom practices to modern technological learning experiences. In relation to this context, this research seeks to explore the perceptions of the use of a blended learning approach to improve student performance in web development courses in selected South African education institutions. The result of this research indicates online presence of content created by the lecturers for the students. This is just mere presence of courses on the technologies available in the higher education institutions. It does not show the proper integration of traditional face-to-face approach and a BL approach. The traditional classroom still prevails despite the advantages and success of use of a BL approach. Lecturers can be regarded as having technological content knowledge (TCK) and failing to integrate it with pedagogical knowledge. There is need for the lecturers to be trained on the Blended Learning Curriculum model (BLC). The BLC model focuses on the integration of technology, pedagogy and content. This integration is what is needed for the successful implementation of BL in the various institutions. Successful implementation of a Blended Learning approach will go a long way in improving student pass rates and driving an upsurge in the programme completion rate.